Crazy for love - Dahl, Victoria (HQN Romance, 2010)
After Chloe Turner's fiancé fakes his death in a plane crash, she escapes to a remote island to avoid the paparazzi. And right next door is Max Sullivan, a treasure-hunting millionaire who just might be the cure for Chloe's heartache.